PERFORASI SEPTUM NASAL PADA PASIEN DENGAN LUPUS ERITEMATOSUS SISTEMIK YANG AWALNYA DIDUGA MORBUS HANSEN (Media Dermato Venereologica Indonesiana, 2020)
Morbus Hansen is one of the great imitator skin diseases. The destruction of nasal cartilage, which may lead to nasal septum perforation and saddle nose, can be seen in lepromatous leprosy. Despite its rarity, the acute exacerbation of systemic lupus erythematosus (SLE) can also lead to nasal septum perforation. A 47- year-old female, presented with a 7-year history of prurituc erythematous macules on the scalp, face, chest, back, and both arms. There was also an area of baldness on the scalp. Those lesions enlarged and increased in numbers gradually. There were cicatricial alopecia, moon face, saddle nose, and nasal septum perforation, without any peripheral nerves thickening. Slit skin smear examination revealed no acid-fast bacilli . Anti- nuclear antibody, anti-dsDNA, and anti-nucleosome were reactive. The histopathological findings and direct immunofluorescence result supported the diagnosis of chronic cutaneous lupus erythematosus (CCLE). The patient was advised to avoid excessive sun exposure and apply sunscreen regularly. She was treated with topical corticosteroid, methylprednisolone, chloroquine, and azathioprine. The involvement of nasal mucosa may be ignored and need more attention in assessing patients with SLE.